Determinants of the Double Burden of Malnutrition at the Community Level in Bangladesh (P10-084-19). (13th June 2019) - Islam, Qumrun; Ali, Masum; Alam, Md; Waid, Jillian
Abstract: Objectives: We use a community-level analysis to better understand the determinates of the nutrition transition in Bangladesh. Methods: We utilize data from the nationally representative Food Security and Nutrition Surveillance Project collected in 13 rounds (2011–2015) in 4413 communities. Definitions of women's overweight/obesity were BMI >23.0 and child undernutrition was height for age z-score <-2 standard deviations from the mean. Communities were divided into four categories: healthy (stunting <30%, overweight <30%), modern (stunting <30%, overweight ≥30%), undernourished (stunting ≥30%, overweight <30%), and double burden (stunting ≥30%, overweight ≥30%). Logistic regression analysis was used to determine which factors were associated with community adherence to each category. Results: Over the period from 2011 to 2015, the proportion of women overweight increased from 30% to 40%, and the proportion of children stunted declined from 40% to 35%. There was a large reduction of the proportion of the population living in undernourished communities (47% to 24%) and a sizable increase in the proportion of the population in modern communities (17% to 36%). The proportion of the population in communities with a double burden of malnutrition increased from 24% to 30%. In multivariable logistic regression models, only wealth, household diets, and division of residence were significant determinants across community nutritional categorization. Healthy communities were characterized by fewer households in the wealthiest quintile and data collection prior to 2015. The odds of a community having a modern nutritional structure increased with the wealth of the area and increasing household dietary diversity. The odds of a community having an undernourished nutritional structure decreased with increasing wealth. A higher proportion of the population in the lowest wealth quintile and household dietary diversity was negatively associated with communities with a double burden of malnutrition. Conclusions: Results indicate that the double burden of malnutrition is not associated with urban residence, pointing to a need for programs in rural as well as urban areas. In addition, the rapid increase in the population living in modern communities points to a need to increase behavior change communication around what is needed for a healthy adult diet. Funding Sources: This publication has been produced with the assistance of the European Union and the UK Department for International Development. The contents of this publication are the sole responsibility of its authors and do not necessarily reflect the views of the European Union or the UK Department for International Development. Supporting Tables, Images and/or Graphs: